ANALISIS TINGKAT KESEHATAN BANK DENGAN PENDEKATAN RISK BASED BANK RATING (RBBR) PADA PT BANK RAKYAT INDONESIA (PERSERO) TBK - Eva Malina Simatupang; Vargo Christian L. Tobing (JURNAL AKUNTANSI BARELANG, 2026)
The assessment of a bank's soundness level is a crucial aspect in evaluating the performance and stability of a financial institution. This study aims to analyze the soundness level of PT Bank Rakyat Indonesia (Persero) Tbk for the period 2020–2024 using the Risk Based Bank Rating (RBBR) approach, which consists of four main components: Risk Profile, Good Corporate Governance (GCG), Earnings, and Capital. This research employs a descriptive quantitative method with documentation techniques, collecting annual financial report data from the official website of PT Bank Rakyat Indonesia (Persero) Tbk. The analysis was conducted on ratios representing each component, such as NPL, LDR, ROA, NIM, CAR, and GCG assessment through self-assessment. The results indicate that PT Bank Rakyat Indonesia (Persero) Tbk has consistently maintained its soundness level within the “very healthy” category for five consecutive years. This reflects the management's ability to maintain asset quality, effective corporate governance, profitability, and capital adequacy. This study is expected to serve as an evaluation material and reference for the company in maintaining sustainable financial performance